Dissolved organic carbon in the South China Sea and its exchange with the Western Pacific Ocean. (December 2015) - Wu, Kai; Dai, Minhan; Chen, Junhui; Meng, Feifei; Li, Xiaolin; Liu, Zhiyu; Du, Chuanjun; Gan, Jianping
Abstract: Based on a large and high quality dataset of total organic carbon (TOC, an approximation of dissolved organic carbon) collected from three cruises in spring, fall and winter in 2009–2011, we examined the distribution of TOC and its seasonality in the oligotrophic regime of the Northern South China Sea (NSCS) as well as its exchanges with the West Philippine Sea (WPS) in the Northwest Pacific Ocean through the Luzon Strait, the only deep channel linking the South China Sea (SCS) and the Pacific Ocean. Surface TOC concentration in the slope and basin areas of the NSCS varied from 65 to 75 μmol L −1 with relatively high values in the northeast part (southwest of Taiwan Island) in spring, and in the eastern parts of the NSCS during fall and winter. The TOC inventory in the upper 100 m of the water column ranged from 6.0–7.5 mol m −2 with a similar distribution pattern as the surface TOC concentration. There were two most significant differences in the TOC profiles between the SCS and the WPS. One was in the upper 200 m, where more TOC was accumulated in the WPS; the other was in the intermediate layer at ~1000–1500 m, where the gradient of TOC concentration was still persistent below 1000 m in the SCS, a feature which did not exist in the WPS. At this intermediate layer, there also appeared an excess of TOC in the SCS as compared with that in the WPS. The TOC concentration below 2000 m in the SCS was identical to that in the Northwestern Pacific, both of which were ~40 μmol L −1 without significant difference among stations and seasons, suggesting that this deep water TOC was homogeneously distributed in the deep SCS basin owing to the fast replenishment of the deep water from the WPS. We adopted an isopycnal mixing model to derive the water proportion contributed respectively from the SCS and Kuroshio along individual isopycnal plane and examined the impact of the Kuroshio intrusion on the TOC in the NSCS. The upper 100 m TOC inventory in the NSCS was overall positively correlated with the Kuroshio water fraction, suggesting that the Kuroshio intrusion enhanced the TOC inventory thereby significantly influencing TOC distribution in the NSCS. Following the sandwich structure of water exchange through the Luzon Strait, with an inflow in the surface and deep layer but an outflow from the SCS in the intermediate layer, we conducted a first order estimation of the TOC transport fluxes based on the reported cross strait volume transport. The TOC transport flux was −107.1±54.6, 54.7±15.0 and −16.4±13.1 Tg C yr −1 at the upper, intermediate and deep layer, respectively. Note that the positive sign means that the flux was from the SCS to the WPS. By integrating the three-layers, the total net transport flux of TOC through the Luzon Strait would be −68.8±58.0 Tg C yr −1 . Because of the great spatial–temporal variability of the water flow across the Luzon Strait, these first order TOC flux estimates were subject to large uncertainty. Nevertheless, because the SCS is featured by higher DOC production, the exchange of these fluxes with the open ocean interior where DOC would have experienced more degradation would have important implications for both the microbial community in the ocean interior and overall carbon cycle in the SCS.